Going back to basics: effectiveness of reading english newspaper on vocabulary knowledge of Malaysian secondary level ESL/EFL students - Thiagarajah, Ambiga; Razali, Abu Bakar (Human Resources Management Academic Research Society (HRMARS), 2021)
This research investigates the effectiveness of English newspaper on vocabulary knowledge of Malaysian secondary school students in an international school in Malaysia. The researchers utilized a quasi-experimental research design with the non-equivalent control group design. As many as 69 students in Year 7 participated in this research. These participants formed the control intact group and experimental intact group in an international secondary school in an urban setting in Lembah Klang, Malaysia, and they came from the same age group and English proficiency level. The collection of data was done through the pre- and post-tests and survey questionnaire. The data were analysed using paired samples T-test and descriptive statistics. The findings of the research indicated that the use of English newspaper as part of the lesson has improved the vocabulary knowledge of the Year 7 students (mean for pre-test: 18.92; mean for post-test: 23.39). They also have their preferred reading genres (i.e., movie and entertainment news, sudoku and puzzles, comic, and modern gadgets technology) as well as positive perceptions to reading the newspaper. The researchers provide some suggestions for future practice and research with regards to the use of newspapers for ESL/EFL students to improve their vocabulary knowledge.